Moderate character education in a multireligious region: an informal approach to religious moderation - Umar, Mardan; Nurhayati, Nurhayati; Ismail, Feiby (TARBAWY: Indonesian Journal of Islamic Education, 2023)
Teenagers as a big part in this country have an important role in building a safe and peaceful life amidst religious differences. Therefore, moderate character must be instilled in adolescents from an early age. This study examines how character education efforts are made for youth in multi-religious areas and what steps can be taken so that moderate character education can be accepted by the millennial generation. This study aims to reveal character education efforts in multi-religious areas and to design a new approach to character education for the millennial generation. This research was conducted using a descriptive qualitative approach with data collection techniques through observation and interviews. Adolescents from different religious backgrounds are gathered in one location to be trained in the understanding and acceptance of religious differences. The results of this study indicate that youth character education in multi-religious areas can be carried out using an informal approach through camps and youth-based activities such as games between heterogeneous groups of adolescents.Remaja sebagai bagian besar di negeri ini mempunyai peran penting dalam membangun kehidupan yang aman dan damai di tengah perbedaan agama. Oleh karena itu, karakter moderat harus ditanamkan pada remaja sejak dini. Penelitian ini mengkaji bagaimana upaya pendidikan karakter yang dilakukan bagi generasi muda di wilayah multi agama dan langkah apa saja yang dapat dilakukan agar pendidikan karakter moderat dapat diterima oleh generasi milenial. Penelitian ini bertujuan untuk mengungkap upaya pendidikan karakter di wilayah multi agama dan merancang pendekatan baru pendidikan karakter bagi generasi milenial. Penelitian ini dilakukan dengan menggunakan pendekatan deskriptif kualitatif dengan teknik pengumpulan data melalui observasi dan wawancara. Remaja yang berbeda latar belakang agama dikumpulkan dalam satu lokasi untuk dilatih pemahaman dan penerimaan terhadap perbedaan agama. Hasil penelitian ini menunjukkan bahwa pendidikan karakter remaja di wilayah multi agama dapat dilakukan dengan pendekatan informal melalui perkemahan dan kegiatan berbasis remaja seperti permainan antar kelompok remaja yang heterogen.